Pembelajaran Mendalam Sebagai Inovasi Dalam Pengajaran Menyimak Teks Bahasa Indonesia Di Sekolah Dasar - Ni Putu Sumertiani (Jurnal Sultra Elementary School, 2025)
This study, entitled "Deep Learning as an Innovation in Teaching Listening to Indonesian Texts in Elementary Schools," aims to describe the effectiveness of the deep learning approach as a pedagogical innovation in improving elementary school students' listening skills. The research method used is a literature study by reviewing various recent scientific sources, such as national and international journals published in the 2023–2025 period. The results of the study indicate that deep learning can significantly improve listening skills by positioning students as active subjects who discover the meaning of the text independently. Through higher-order thinking processes, students not only understand the text's content literally but also interpret implied meanings, assess moral messages, and relate the text's content to personal experiences. This approach creates a collaborative and reflective learning atmosphere, where interaction between students and teacher guidance play a vital role in deepening understanding. In addition, deep learning also increases students' motivation and interest in learning because it provides space for exploration, reflection, and recognition of individual perspectives. The results of previous research support that the application of deep learning is effective in developing active, creative, and responsible learning characters. Thus, this approach is relevant for implementation in Indonesian language learning in elementary schools because it aligns with the spirit of the Independent Curriculum, which emphasizes meaningful learning, critical thinking, and student-centeredness.